Associations of a body shape index, weight-adjusted waist index with the activities of daily living impairment in the middle-aged and elderly population: results from the China Health and Retirement Longitudinal Study - Du, Yihang; Zhang, Wenjing; Chen, Zizhen; Zhu, Xueping; Lyu, Meng; Wei, Yi; Hu, Yuanhui (Frontiers in Medicine, 2025)
ObjectiveTo investigate and compare the associations of body mass index (BMI), waist circumference (WC), a body shape index (ABSI), weight-adjusted waist index (WWI), and waist-to-height ratio (WHtR) with activities of daily living (ADL) impairment among the middle-aged and elderly population in China.MethodsIn this study, 8,700 participants from 2011 were included in the cross-section analysis. The prospective study used baseline data from 2011 and follow-up data from 2013, 2015, 2018, and 2020, with a total of 5,945 participants included. Binary logistic regression models were employed in the cross-sectional study to calculate odds ratio (OR) with corresponding 95% confidence interval (95% CI). In the prospective study, Cox proportional hazards regression models were utilized to estimate hazard ratio (HR) with 95% CI. Restricted cubic spline curve was used to identify trends, with subgroup analysis performed. Diagnostic performance was quantified through receiver operating characteristic curve analysis, with area under the curve values computed.ResultsIn the cross-sectional study, BMI (OR = 0.98, 95% CI: 0.97–1.00) was significantly negatively associated with ADL impairment risk, while ABSI (OR = 1.25, 95% CI: 1.14–1.37), WWI (OR = 1.16, 95% CI: 1.09–1.24) were positively associated with ADL impairment. However, there was no significant association between WC, WHtR and ADL impairment. In the prospective study, WC, WHtR and BMI showed no significant association with ADL impairment, while ABSI (HR = 1.07, 95% CI: 1.01–1.14) and WWI (HR = 1.05, 95% CI: 1.01–1.10) remained positively associated with ADL impairment. Positive linear correlations were observed among ABSI, WWI, and ADL impairment and there was no difference among subgroup variables. The predictive ability of WWI was slightly higher than ABSI, with an AUC value of 0.598.ConclusionABSI and WWI were significantly associated with the risk of ADL impairment among the middle-aged and elderly population in China. ABSI and WWI had the potential to serve as superior obesity indicators for identifying individuals at higher risk for ADL impairment.